Modification of female and male social behaviors in estrogen receptor beta knockout mice by neonatal maternal separation - Tsuda, Mumeko C.; Yamaguchi, Naoko; Nakata, Mariko; Ogawa, Sonoko (Frontiers in Neuroscience, 2014)
Maternal separation (MS) is an animal model mimicking the effects of early life stress on the development of emotional and social behaviors. Recent studies revealed that MS stress increased social anxiety levels in female mice and reduced peri-pubertal aggression in male mice. Estrogen receptor (ER) β plays a pivotal role in the regulation of stress responses and anxiety-related and social behaviors. Behavioral studies using ERβ knockout (βERKO) mice reported increased social investigation and decreased social anxiety in βERKO females, and elevated aggression levels in βERKO males compared to wild-type (WT) mice. In the present study, using βERKO and WT mice, we examined whether ERβ contributes to MS effects on anxiety and social behaviors. βERKO and WT mice were separated from their dam daily (4 h) from postnatal day 1 to 14 and control groups were left undisturbed. First, MS and ERβ gene deletion individually increased anxiety-related behaviors in the open field test, but only in female mice. Anxiety levels were not further modified in βERKO female mice subjected to MS stress. Second, βERKO female mice showed higher levels of social investigation compared with WT in the social investigation test and long-term social preference test. However, MS greatly reduced social investigation duration and elevated number of stretched approaches in WT and βERKO females in the social investigation test, suggesting elevated levels of social anxiety in both genotypes. Third, peri-pubertal and adult βERKO male mice were more aggressive than WT mice as indicated by heightened aggression duration. On the other hand, MS significantly decreased aggression duration in both genotypes, but only in peri-pubertal male mice. Altogether, these results suggest that βERKO mice are sensitive to the adverse effects of MS stress on subsequent female and male social behaviors, which could then have overrode the ERβ effects on female social anxiety and male aggression.